Age groups that sustain resurging COVID-19 epidemics in the United States - Monod, M; Blenkinsop, A; Xi, X; Hebert, D; Bershan, S; Tietze, S; Baguelin, M; Bradley, VC; Chen, Y; Coupland, H; Filippi, S; Ish-Horowicz, J; et al. (American Association for the Advancement of Science, 2021)
After initial declines, in mid-2020 a resurgence in transmission of novel coronavirus disease (COVID-19) occurred in the United States and Europe. As efforts to control COVID-19 disease are reintensified, understanding the age demographics driving transmission and how these affect the loosening of interventions is crucial. We analyze aggregated, age-specific mobility trends from more than 10 million individuals in the United States and link these mechanistically to age-specific COVID-19 mortality data. We estimate that as of October 2020, individuals aged 20 to 49 are the only age groups sustaining resurgent SARS-CoV-2 transmission with reproduction numbers well above one and that at least 65 of 100 COVID-19 infections originate from individuals aged 20 to 49 in the United States. Targeting interventions-including transmission-blocking vaccines-to adults aged 20 to 49 is an important consideration in halting resurgent epidemics and preventing COVID-19-attributable deaths.